Finding Ivan Vladislavić - Writing the city - Beilharz, Peter; Supski, S. (2016)
The work of Ivan Vladislavić is well established in his native South Africa, and increasingly recognized on the larger world stage of writing, editing and publishing. If his work nevertheless eludes scrutiny in some quarters, this may also have to do with its nature, and not only with its origin. The works differ and vary; there is no formula or project which proceeds neatly by sequence. No single work can be second-guessed from any other. This is a project full of surprises, connecting variously to art, photography, architecture and to urban studies, setting to work images and practices at once realist and surreal, absurdist and layering, and given to time and place and the universal. How then do we read it, and how does he write? For the purposes of this paper, we explain and locate our enthusiasm with reference to two works, The Restless Supermarket (2001) and Portrait with Keys (2006). We seek to identify some key tropes about place and place-writing and cities and city-writing with reference to Johannesburg and the way in which Vladislavic plays his subjects and his readers, placing not only fiction (or realism) under question but placing writing itself closer to the editor's deletion mark. This may be, we suggest, a kind of writing sideways. © Thesis Eleven Pty, Ltd., SAGE Publications.